Biceps Brachii Muscle Synergy and Target Reaching in a Virtual Environment - He, Liang; Mathieu, Pierre A. (Frontiers in Neurorobotics, 2019)
Upper limb amputees can now have access to prostheses capable of many degrees of freedom, but with a reduced number of muscles, they cannot generate the required many electromyographic (EMG) control signals. When their biceps are still functional, electrodes can be put across the biceps’ width and, with features of muscular synergy extracted from those signals, the control of a modern upper limb myoelectric prosthesis could be facilitated. Here, muscular synergy of the biceps of normal subjects was obtained from 5 surface electrode pairs when their upper limb was in 8 different static postures. With those 8 muscular synergies, a classifier was trained to identify features associated with each limb posture and when a posture taken by a subject is recognized, it is associated with a small sphere movement within a cube presented in a screen. Each cube axis was assigned to the shoulder, elbow and wrist joints of an upper limb and this determined the corner assigned to each of 8 static postures. When a posture is recognized, the red sphere moves toward the corner associated with that posture and with a sequence of different postures, the goal was to reach a target placed in the cube. In a 3D virtual environment and with the developed control system, results obtained with 12 subjects indicate that, it is possible, but not easy to master how to move a small sphere toward a target. As a proof of concept, we show that features of the biceps muscular synergy has the potential to ease the control of upper limb myoelectric prostheses.